COMPARATIVE PHYSICO-CHEMICAL ANALYSIS OF ROOTS OF YELLOW KARWEER (THEVETIA NERIIFOLIA JUSS) BEFORE AND AFTER PURIFICATION PROCESS - Deshpande, *Manasi; Abhijeet B, Patil (International Journal of Ayurveda and Pharma Research, 2018)
Yellow Karweer/ oleander (Thevetia neriifolia synonym Thevetia peruviana) belongs to the family Apocynaceae. It is a poisonous plant, with various pharmacological activities. It is used by Ayurvedic physician in various diseases, especially in the skin disease. Karweer are potentially lethal plants after ingestion. All parts of the plants are toxic and contain a variety of cardiac glycosides. Excess use of Karaweer results in nausea, vomiting, abdominal pain, diarrhoea, dysrhythmia and hypocalcaemia in most cases. Administration of Karweer is recommended only after the Shodhana (purification procedures) in Godugdha (cow’s milk).MethodAfter purification with cow’s milk by boiling method, Yellow Karweer root was evaluated for their pharmacognostical and pharmaceutical analysis. The obtained roots were investigated for their powder microscopically characters, phytochemical characters like preliminary phytochemical screening and Thin layer chromatography as per the API guidelines.ResultsOrganoleptic study shows variations in colour, odour, taste and appearance in all samples after purification. Microscopically study of powder highlights some changes like more number of oil globules in Godugdha (cow's milk) purified sample. Preliminary phytochemical screening reveals the presence of alkaloids, saponin glycoside, flavonoids, reducing sugar, etc.ConclusionThe observed data can be helpful to delineate the impact of purification process on yellow Karweer roots. Media has an important role to reduce the toxic effects and increase the potency.